PENGGUNAAN DATA TORSI UNTUK PENENTUAN PARAMETER MOTOR INDUKSI 3 FASA - Wisasongko Dwi Martianto (Universitas Ahmad Dahlan, 2004)
To predict induction motor performance, induction motor parameters have to be known. This paper proposes 3 phase induction motor parameters determination with input datas, such as locked rotor torque, full load torque, breakdown torque, rated motor voltage, and full load speed, which will produce optimization problems that can be solved with one of the branch of artificial intelligence science, which is genetic algorithms, that is developed rapidly nowadays and well known has a good performance.